The boss [videorecording (DVD)] - McCarthy, Melissa, 1969-; McCarthy, Melissa, 1969-; Falcone, Ben, 1973-; Bell, Kristen, 1980-; Bates, Kathy, 1948- (Universal Pictures Home Entertainment, 2016)
Michelle Darnell a titan of industry is sent to prison after she's caught for insider trading. When she emerges ready to rebrand herself as America's latest sweetheart, not everyone she screwed over is so quick to forgive and forget.